Kesantunan Berbahasa Guru Dalam Proses Pembelajaran Bahasa Indonesia Kelas XI SMA Negeri 8 Padang - Chan, Dwi Mutia; Khairani, Zuraida; Hayati, Najmi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Language politeness is an attitude that must be maintained in communication activities, both speakers and speech partners, in order to produce polite speech, so that between speakers and speech partners can establish good communication. Politeness is a rule of behavior that is determined and agreed upon by a certain society so that politeness is also a prerequisite agreed upon by social behavior. This research aims to describe the form of politeness of the teacher's speech in class XI SMA 8 Padang in the teaching and learning process. Politeness is a form of cultural politeness. The type of research conducted is qualitative research. Research that produces data descriptions in the form of spoken words from the objects observed. To achieve the objectives in accordance with the problem under study, descriptive method is used. Descriptive method is a method that is done by collecting, compiling and analyzing and interpreting data. The data obtained is described to answer research questions. Based on the results of data analysis that has been carried out by researchers, it can be concluded that the form of language politeness of class XI teachers of SMA 8 Padang, there is a more dominant one can be seen below. (1) imperative politeness mode 40 utterances, (2) interrogative politeness mode 37 utterances, (3) declarative politeness mode 33 utterances.